Odpowiedzi

Najlepsza Odpowiedź!
2009-12-01T19:25:29+01:00
(x+3y)²-9y²=x²+6xy+3y²-9y = x(x+6y)+y(y-9)
4x²+1-(2x+1)²=4x²+1-2x²-4x+1=2x²-4x=x(2x-4)
2(3+b)²+12b=2(9+6b+b²)+12b = 18+24b+2b² = 2(9+12b+b²)
(x-2)²-(x+1)²=x²-4x+4-x²-2x+1=-6x+5
(a+2)²+(a-2)²=a²+4a+4+a²-4a+4=2a²+8=2(a²+4)
(b+3)²-(b-3)²=b²+6b+9-b²-6b+9=18
(5m+4n)²-(4m-5n)²=25m²+40mn+16n²-16m²+40mn+25n²=9m²+80mn+41m²=m(9m+80n+41m)
(3x-2)²+2(x+3)² = 9x²-12x+4+2(x²+6x+9)=9x²-12x+4+2x²+12x+18=11x²+22 = 11(x²+2)
(y²+1)²-2(y²-1)²=y³+2y²+1-2(y³+2y²+1)=y³+2y²+1-2y³+4y²+2= -y³+6y+3
(5-0,2k³)²+5(k³-5)=25-2k³+0,4k⁵+5k³-25=3k³+0,4k⁵=k³(3+0,4k²)
2009-12-01T21:52:45+01:00
(x+3y)²-9y²= x²+6xy+9y²-9y²=x²+6xy

4x²+1-(2x+1)²=4x²+1-(4x²+4x+1)=4x²+1-4x²-4x-1=-4x

2(3+b)²+12b=2(9+6b+b²)+12b=18+12b+2b²+12b=2b²+24b+18

(x-2)²-(x+1)²=x²-4x+4-(x²+2x+1)=x²-4x+4-x²-2x-1= -6x+3

(a+2)²+(a-2)²=a²+4a+4+a²-4a+4=2a²+8

(b+3)²-(b-3)²=b²+6b+9-(b²-6b+9)=b²+6b+9-b²+6b-9=12b

(5m+4n)²-(4m-5n)²=
=25m²+40mn+16n²-(16m²-40mn+25n²)=25m²+40mn+16n²-16m²+40mn-25n²=9m²+80mn-9n²

(3x-2)²+2(x+3)²=9x²-12x+4+2(x²+6x+9)=9x²-12x+4+2x²+12x+18=
=11x²+22

(y²+1)²-2(y²-1)²=y⁴+2y²+1-2(y⁴-2y²+1)=y⁴+2y²+1-2y⁴+4y²-2=
=-y⁴+6y²-1
(5-0,2k³)²+5(k³-5)=25-2k³+0,04k⁶+5k³-25=3k³+0,04k⁶